Drug‐eluting stents versus bare metal stents prior to noncardiac surgery. Issue 4 (20th August 2014) - Bangalore, Sripal; Silbaugh, Treacy S.; Normand, Sharon‐Lise T.; Lovett, Ann F.; Welt, Frederick G.P.; Resnic, Frederic S.
<x xml:space="preserve">Abstract</x> Background The safety of drug‐eluting stents (DES) vs. bare metal stents (BMS) in the perioperative setting, a heightened state of inflammation and thrombosis is not well defined. Methods All adults undergoing noncardiac surgical (NCS) procedures within 1 year following percutaneous coronary intervention (PCI) in Massachusetts between April 1, 2004, and September 30, 2007, were identified from an administrative claims database. Patients were divided into those who received BMS vs. DES at index PCI. Primary net clinical outcome was death, myocardial infarction (MI) or bleeding within 30 days of NCS. Primary clinical outcome was 30‐day death or MI. Results Among 8, 415 (22% BMS) patients that satisfied our inclusion criteria, 1, 838 BMS patients were matched with 3, 565 DES patients with similar propensity scores. In the DES cohort, the 30‐day primary net clinical outcome rate was lower with longer time from PCI to NCS (P = 0.02) with lowest rates if NCS was performed after 90 days from PCI (event rate 8.57, 7.53, 5.21, and 5.75% for 1–30, 31–90, 91–180, and 181–365 days from PCI to NCS). However, in the BMS cohort, the event rate was uniformly high regardless of the time from PCI to NCS (P = 0.60) (event rate 8.20, 6.56, 8.05, and 8.82% for 1–30, 31–90, 91–180, and 181–365 days from PCI to NCS). There was no significant difference between DES and the BMS group for 30‐day primary net clinical outcome (6.64 vs. 7.89%; P = 0.10), but there was a 26% lower odds of primary clinical outcome (OR = 0.74, 95% CI 0.58–0.94) with DES when compared with BMS, driven mainly by differences in event rates when NCS was performed >90 days post PCI. Conclusion DES implantation was not associated with higher adverse events after NCS. Moreover, the incidence of adverse events following NCS was lower when NCS was performed >90 days post‐DES implantation suggesting that it may not be necessary to wait until 12 months post PCI with DES before NCS. © 2014 Wiley Periodicals, Inc.